Legal Reconstruction of State Institutionalities of State Commissions to Suppress the Potential of Institutional Authority Dispute - Hakim, Lukman (International Journal of Criminology and Sociology, 2021)
The main problem of this research triggers by the fact that Indonesia fundamental constitutional system changed into the 1945 Constitution. The changes affected the structure and structural mechanism of state institutions. The main purpose of this study is to analyze the philosophical question of the basic root formed in the 1945 Constitution as a new constitution of Indonesia. Regarding the organization and institution of the state can be started by questioning the essence of power that is institutionalized or organized into the state. The results showed that it is also important to know how the principle of popular sovereignty is reflected in the structure and mechanisms of state and government institutions that guarantee the establishment of the legal system and the functioning of the democratic system. At the theory level in terms of state institutions, with the various state commissions, how the principle of popular sovereignty is organized into institutional functions can be patterned into state institutions that are equal and mutually balanced in forms of checks and balances. From a normative perspective, the sources of state institutional authority can be used as a reference in the structuring of state institutions by considering shifts and the development of state administration, especially with the state commissions that occurred after changes to the 1945 Constitution.